Research on the classification of calculation schema of the column-foundation connections - Su-Haeng, Ju; Mun Il, Jong; TokGo, Jun (International Journal of Architecture and Urbanism, 2026)
Recently, the steel structures are made by light-gauge steel structures so in many cases column base is solved by exposed column base in buildings such as industrial buildings. Considering the column- foundation connections exactly is very important to secure the safety of structure because the reality and theory is so different. So the aim of the study is to verify the deformation behavior of the various column base which is designed and constructed by exposed column base and to analyze the factors affect to rotational stiffness of the column base. And on the basis of this, the formula of the rotational stiffness which can be used in design is determined. And also the criterion of classification which can classify the joint of steel column and foundation into hinge, rigid and semi-rigid column base is established.